HDAC9 Silencing Exerts Neuroprotection Against Ischemic Brain Injury via miR-20a-Dependent Downregulation of NeuroD1 - Zhong, Liangjun; Yan, Jinxiang; Li, Haitao; Meng, Lei (Frontiers in Cellular Neuroscience, 2021)
Cerebral stroke is an acute cerebrovascular disease that is a leading cause of death and disability worldwide. Stroke includes ischemic stroke and hemorrhagic strokes, of which the incidence of ischemic stroke accounts for 60–70% of the total number of strokes. Existing preclinical evidence suggests that inhibitors of histone deacetylases (HDACs) are a promising therapeutic intervention for stroke. In this study, the purpose was to investigate the possible effect of HDAC9 on ischemic brain injury, with the underlying mechanism related to microRNA-20a (miR-20a)/neurogenic differentiation 1 (NeuroD1) explored. The expression of HDAC9 was first detected in the constructed middle cerebral artery occlusion (MCAO)-provoked mouse model and oxygen-glucose deprivation (OGD)-induced cell model. Next, primary neuronal apoptosis, expression of apoptosis-related factors (Bax, cleaved caspase3 and bcl-2), LDH leakage rate, as well as the release of inflammatory factors (TNF-α, IL-1β, and IL-6) were evaluated by assays of TUNEL, Western blot, and ELISA. The relationships among HDAC9, miR-20a, and NeuroD1 were validated by in silico analysis and ChIP assay. HDAC9 was highly-expressed in MCAO mice and OGD-stimulated cells. Silencing of HDAC9 inhibited neuronal apoptosis and inflammatory factor release in vitro. HDAC9 downregulated miR-20a by enriching in its promoter region, while silencing of HDCA9 promoted miR-20a expression. miR-20a targeted Neurod1 and down-regulated its expression. Silencing of HDAC9 diminished OGD-induced neuronal apoptosis and inflammatory factor release in vitro as well as ischemic brain injury in vivo by regulating the miR-20a/NeuroD1 signaling. Overall, our study revealed that HDAC9 silencing could retard ischemic brain injury through the miR-20a/Neurod1 signaling.